Analgesic and Anti-Inflammatory Activities of Ethyl - verma, rajesh (International Journal of Pharmaceutical & Biological Archive, 2010)
The leaves of Salvadora persica L. were extracted with petroleum ether, chloroform, and ethyl acetate, ethanol, and water solvents. The ethyl acetate extract was screened for analgesic and anti-inflammatory activities. The analgesic activity was carried out by tail immersion method and anti-inflammatory activity was evaluated by carrageen induced paw edema method. Pretreatment with ethyl acetate extract (500 mg / kg, body weight) showed significant analgesic activity (p< 0.01) comparable to the standard drug pentazocine and against carrageen induced paw edema suppressant activity comparable to the standard drug indomethacin.